Ideal extraction temperature for antioxidants from holy basil and bunching onion - Khattak, Muhammad Muzaffar Ali Khan; Abidin, Adlina Zainal; Azahari, Nuraniza (Progress in Nutrition, 2019)
This study aimed to determine ideal temperature for antioxidants from holy basil and bunching onion. Holy Basil (Ocimum Tenuiflorum) and Onion (Allium Fistulosum) were extracted with various temperatures ranging from 75 – 100 °C with two solvents i.e. methanol and water (room temperature & boiling). Total phenolic contents (TPC) and total flavonoid contents (TFC) were determined in the extracts by using the Folin-Ciocalteau and Aluminum chloride complex formation assays respectively. Extracts were analyzed in triplicates statistically compared using one-way analysis of variance (ANOVA) and the difference between the mean was ascertained at 95% confidence interval (P